MULTIPLE EDIFICE-COLLAPSE EVENTS IN THE EASTERN MEXICAN VOLCANIC BELT: THE ROLE OF SLOPING SUBSTRATE AND IMPLICATIONS FOR HAZARD ASSESSMENT - Carrasco-Núñez G.; Díaz-Castellón R.; Siebert L.; Hubbard B.; Sheridan M.F.; Rodríguez S.R. (My University, 2006)
The Citlaltépetl-Cofre de Perote volcanic chain forms an important physiographic barrier that separates the Central Altiplano (2500 masl) from the Gulf Coastal Plain (GCP) (1300 masl). The abrupt eastward drop in relief between these provinces gives rise to unstable conditions and consequent gravitational collapse of large volcanic edifices built at the edge of the Altiplano. Eastward sloping substrate, caused by the irregular configuration of the basement rocks, is the dominant factor that controls the direction of collapsing sectors in all major volcanoes in the region to be preferentially towards the GCP. These collapses produced voluminous debris avalanches and lahars that inundated the well-developed drainages and clastic aprons that characterize the Coastal Plain. Large catastrophic collapses from Citlaltépetl, Las Cumbres, and Cofre de Perote volcanoes are well documented in the geologic record. Some of the avalanches and transformed flows have exceptionally long runouts and reach the Gulf of Mexico traveling more than 120 km from their source. So far, no direct evidence has been found for magmatic activity associated with the initiation of these catastrophic flank-collapses. Apparently, instability of the volcanic edifices has been strongly favored by very intense hydrothermal alteration, abrupt topographic change, and intense fracturing. In addition to the eastward slope of the substrate, the reactivation of pre-volcanic basement structures during the Late Tertiary, and the E-W to ENE-SSW oriented regional stress regimes may have played an important role in the preferential movement direction of the avalanches and flows. In addition to magmatic-hydrothermal processes, high amounts of rainfall in the area is another factor that enhances alteration and eventually weakens the rocks. It is very likely that seismic activity may be the principal triggering mechanism that caused the flank collapse of large volcanic edifices in the Eastern Mexican Volcanic Belt. However, critical pore water pressure from extraordinary amounts of rainfall associated with hurricanes or other meteorological perturbation cannot be ruled out, particularly for smaller volume collapses. There are examples in the area of small seismogenic debris flows that have occurred in historical times, showing that these processes are not uncommon. Assessing the stability conditions of major volcanic edifices that have experienced catastrophic sector collapses is crucial for forecasting future events. This is particularly true for the Eastern Mexican Volcanic Belt, where in many cases no magmatic activity was associated with the collapse. Therefore, edifice failure could occur again without any precursory warning. © 2006 Elsevier B.V. All rights reserved.
Keywords: DEBRIS AVALANCHE; EDIFICE COLLAPSE; INSTABILITY; MEXICAN VOLCANIC BELT; VOLCANIC HAZARDS